Pneumatikus izomelemek alkalmazása gyógyterápiás eszközökhöz - Sárosi, József; Gyeviki, János (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
Many important activities of daily living (e. g. dressing and eating) depend on two-handed function. For people affected by stroke, frequent physical therapy has been suggested to be a successful rehabilitation. The use of robotic devices to assist the therapies is becoming more commonly, but traditional robots are usually stiff. The devices have to be able to provide the treatment way of repetitive practice. More and more devices consist of pneumatic artificial muscles (PAMs) as a good solution for actuators. There is a need for affordable, economical, low cost, lightweight, practical, low stiffness, multi-dimensional and low noise operation devices to assist therapy. In this paper we present some possibilities of use of PAM in rehabilitation devices.